Generic software development framework for enterprise resource planning system development - Zughoul, Basem Yousef Mofadi (2014)
Traditional software systems are developed in house to fit with a specific set of functions, but it does not comply with various business needs, like expanding markets, increasing competition and technology developments. Many organizations rely on Enterprise Resource Planning (ERP) systems to manage and process their entire business requirements, including a large size of applications. However, many ERP system implementations failed or were terminated abruptly, because of budget overrun, high business risks under extend scope of work, and takes a long time to implement. Most of the works include dealing with customization off-the-shelf ERP package, or changing organization business process to suite with the package. This thesis proposed a software development framework to develop traditional systems to ERP systems. The aim of this framework is to provide a solution for software companies to develop ERP systems from their own perspectives, and according to specific ERP characteristics to fulfill their business needs. The framework utilizes the software development life cycle focusing on functionality, procedures and business needs in organizations, based on the specific ERP characteristics. The proposed framework is verified by two case studies and survey questionnaires to get feedback from software companies experts on the suitability of the framework implementation in the organizations. The results indicated that around 81.86% found the framework is suitable for their needs. This thesis contributes to the body of knowledge on in-house development of ERP systems based on organizational perspective, business functionality, and best practices.